Update on Indonesia’s East Java Province: Still a Case of ‘Balanced Development’? - McMichael, Heath (OECONOMICUS Journal of Economics, 2022)
Since the 1980s, surveys have portrayed East Java Province as an economic success story, with high levels of growth spread across all major sectors in rural as well as urban settings. East Java appears a victim of its own success with large-scale investors in the processed food sector considering relocating to Central Java where minimum wages are lower. In terms of domestic investment, housing, industrial estates and offices (27 per cent), transportation and warehousing (14 per cent) and food (8 per cent) were the main destinations in Q1 22. In Q2 2022, the principal sources of foreign investment were the United States (43 per cent, comprising mainly PT Freeport Indonesia’s Rp 5 trillion realised investments in its Gresik copper smelter), Hong Kong (19 per cent), Singapore (15 per cent) and Japan (9 per cent). Another aspect of the balanced development thesis was that trade was not the driving force in growth. That still seems to be so. Input-output analysis appears to show that the province’s surplus is actually not very large – suggesting a high degree of complementarity between East Java’s agricultural, manufacturing and export sectors. While the balanced development thesis was never meant to imply that East Java’s regions had experienced a uniform stage of development, it is possible to identify ‘winners’ and ‘losers’ within the province. So, what is East Java’s future trajectory and does it continue to deserve a reputation for balanced development? In terms of investment, balance may still be the hallmark of provincial development. In order to navigate through the ‘middle-income trap’, the province will need to invest more in human capital to foster entrepreneurship, productivity and wellbeing. Management of the provincial economy will be increasingly difficult as the intricate and complex nexus of politics and business in the province evolves.